Regulation of the terminal maturation of iNKT cells by mediator complex subunit 23 - Yu Xu (Nature Portfolio, 2018)
Invariant Natural Killer T cells (iNKT) rapidly exert effector functions upon activation, but the mechanisms of their functional maturation remain to be determined. Here, Xu and colleagues show that the mediator subunit Med23 is a transcriptional regulator controlling iNKT cell terminal maturation.